Spectral occupancy rate of cognitive radio networks in queueing with adaptive modulation and coding over multiple‐input and multiple‐output transmit antenna selection/maximal ratio combining in Nakagami‐m fading. Issue 2 (1st June 2014) - Jang, Won Mee; Chang, Woan Sun
Abstract : Cognitive radio is successfully overlayed on the single user cross‐layer design and implementation with adaptive modulation and coding (AMC) over frame‐slotted transmission. The authors analyse the spectral occupancy rate of cognitive radio networks with AMC and queueing effect. They employ multiple‐input and multiple‐output with single transmit antenna selection and maximal ratio combining in Nakagami‐ m fading channel. The average spectral efficiency and packet dropping rate are also obtained. The analytical result shows that significant cognitive radio traffic can be accommodated without compromising the primary user network quality.